Banana Product Development in the Women Farmers Group (KWT) Mertelu Village, Gunungkidul - Harmini, Sri; Suharman, Suharman; Nadia, Lana Santika (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Gedangsari District is one of the sub-districts in Gunungkidul Regency, Yogyakarta which is classified as underdeveloped. This sub-district has potential but has not developed optimally because its human resource capabilities have many limitations. The livelihood of the people in Mertelu Village is farming. The Mertelu region has a field area of 101.68 hectares which is mostly used by the community to grow bananas. Steep topographic conditions cause people's access to mobility to be hampered. This affects the economic conditions of the community, especially in expanding sales targets for agricultural products. So selling to the public is still within a narrow scope. Most of the banana harvest is only consumed for personal use and sold raw if the harvest is large enough. It is hoped that the development of food products can provide variations in finished products so that they have a high selling value and can cover the shortage of terrain in the Mertelu area. Therefore, an innovative approach is needed in solving socio-economic problems in the village. One of the proposed approaches is community empowerment through increasing skills in banana processing production. It is hoped that this method can make a positive contribution in improving the quality of life of the people in Mertelu Village by empowering women, especially the Batur Indah Women Farming Group (KWT).